Neo-liberalism Theory: Trilateral Relations of Iran-China and Saudi Arabia - Butt, Saima; Bhatti, Tanzeela Aziz (Annals of Human and Social Sciences, 2024)
This article deals with the emergence alliance between Iran-Saudi Arabia and China which is significant for the Middle Eastern economy. The objective of this study is to analyze the potential opportunities and the challenges that each country may face in terms of economic integration and collaboration. The neoliberal approach is applied by the researcher to investigate China’s interest and especially economic cooperation with both states. In order to understand the economic cooperation of Iran-Saudi Arabia and China, qualitative methodology i.e. historical and descriptive types of research are been applied. Moreover, secondary sources of data collections are been used. The study shows that the post-deal relations between Suadi arabia and Iran has been improved and further paves the way for stabilizing middle eastern region with assistance of China. It is recommended that both muslim states should comply with international standards while cooprtatiing with China to maintain regional peace and stability.